SENSITIVITY OF THE TECHNICAL CONDITION OF ELECTRICAL EQUIPMENT OF MOBILE ROBOTIC COMPLEXES FOR SOLVING MONITORING TASKS - A.V. Zayara; M.E. Danilin (Надежность и качество сложных систем)
Background. To solve the problem of sensing the technical condition of the electrical equipment of mobile robotic complexes through the integration of sensory information, a monitoring procedure is proposed as an integral part of a maintenance and repair system based on a proactive concept. Materials and methods. Using the method of associative analogy, a comparison of the time-deterministic process of reducing the performance of the robotics complex with a deterioration in human performance has been carried out, which makes it possible to assess the technical condition according to a generalized parameter characterizing the energy efficiency of the RTK using fuzzy logical inference. Results and conclusions. In the process of simulating such a cognitive function of a person as the perception of well-being, a numerical assessment of the complex's current technical condition by the control system is implemented.